End combustion products of mixtures of ultrafine aluminum powder with zirconium-aluminum alloy powder in air; Combustion, Explosion, and Shock Waves; Vol. 36, № 2 - Ilyin A. P. Aleksandr Petrovich; An V. V. Vladimir Vilorievich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Yablunovski G. V. (2000, 2000)
Title screen